Theophylline and Caffeine as Alternatives During an Aminophylline Shortage. Issue 3 (March 2019) - Singleton, Emily L.; Le, Nancy; Ness, Genevieve Lynn
The latest aminophylline shortage has prompted a need for alternative reversal agents for pharmacological stress testing. Cardiac stress testing is common for diagnosis and prognosis in patients with coronary heart disease. Options for pharmacological stress test agents include adenosine, regadenoson, dipyridamole, and dobutamine, whereas aminophylline is the recommended reversal agent. Adenosine and dobutamine can be used as alternatives to regadenoson and dipyridamole to decrease or eliminate the use of aminophylline. Alternatives to aminophylline include theophylline and caffeine. It is important to efficiently identify alternatives during a drug shortage to maintain optimal patient outcomes.